Plan de marketing para la empresa franquiciado Disensa Juan A. Altamirano del cantón Catamayo - Rojas J., Yasmin (2016)
Research on "MARKETING PLAN FOR BUSINESS FRANCHISEE DISENSA JUAN A. CANTON ALTAMIRANO CATAMAYO” was developed in the city of Catamayo, with the overall objective of developing a marketing plan in order to improve the economic and competitive company as the marketing plan is an essential tool in any organization, as it facilitates effective marketing of any product or service. It is very risky to try a company succeed without having previously developed a marketing plan. This research includes: Summary, which corresponds to a summary of the relevant parts of the thesis, the Introduction, this highlights the importance of the research topic, in which you will have a comprehensive understanding of all the work done, the Review literature, it contains citations containing theoretical contexts about the marketing plan, including: its concepts and importance of the most used in the present work, we continued the Materials and Methods in which details methods: deductive, inductive, descriptive techniques such as direct observation, interview and survey procedures used in the investigation that led to collect the information necessary to determine facts and phenomena that occur in the business environment and identify the key internal and external problems affecting the same, the same that have prevented its normal solvency and development. The results, which are part, detailing the internal and external analysis of the company "DISENSA JUAN A. ALTAMIRANO": a historical, organizational structure etc... Then performed a SWOT analysis of the company, which were determined as internal factors are the strengths and weaknesses and the external factors are the threats and opportunities, and then makes the array of high-impact criteria and assessment with their respective percentages. Based on the results I obtained the talk, in which a proposal was made Marketing Plan to improve the business of DISENSA JUAN A. ALTAMIRANO, this consists the following objectives: Company Franchisee Disensa John A. Canton Altamirano Catamayo with their product lines achieved recognition in the market town of Catamayo, Get a competitive price suitable for the level of quality offered in the product and services to sell, this through reengineering price Achieve bigger and better market coverage to better serve customers in the Canton and the goal of advertising program revolves around a main parameter: transmitting a communication (message) specific to a certain audience with a level of performance that must be achieved in a short period of time. Finally most important conclusions of the investigation with their recommendations, described the most important situations obtained during the application of analysis of all the research work, so that the manager take the necessary corrective action to benefit their organization; Bibliography, is the part where you have to know the sources of information used in the development of this work and are last Annexes.